A bivalent tarantula toxin activates the capsaicin receptor, TRPV1, by targeting the outer pore domain - Bohlen, Christopher J.; Priel, Avi; Zhou, Sharleen; King, David; Siemens, Jan; Julius, David (Cell, 2010)
Toxins have evolved to target regions of membrane ion channels that underlie ligand binding, gating, or ion permeation, and have thus served as invaluable tools for probing channel structure and function. Here we describe a peptide toxin from the Earth Tiger tarantula that selectively and irreversibly activates the capsaicin- and heat-sensitive channel, TRPV1. This high avidity interaction derives from a unique tandem repeat structure of the toxin that endows it with an antibody-like bivalency, illustrating a new paradigm in toxin structure and evolution. The ‘double-knot’ toxin traps TRPV1 in the open state by interacting with residues in the presumptive pore-forming region of the channel, highlighting the importance of conformational changes in the outer pore region of TRP channels during activation.